Determinação de farmacos em efluentes hospitalares utilizando UHPLC-QTOF MS, UHPLC-MS/MS e avaliação dos quocientes de risco ambiental - Mühlen, Lisandro von (2023)
One of the main sources of pollution of aquatic systems by drugs is the incorrect disposal of hospital effluents (HWW). The HWW matrix is quite complex and therefore its analysis is a challenge, in this context, sample preparation plays an important role in the determination of these substances. The combination of DSPE and SPE techniques was evaluated in the preparation stage of HWW samples, from two hospitals (HA and HB) in Porto Alegre (RS, Brazil), and the use of a method of direct injection of samples from a hospital (HC) in Santa Maria (RS, Brazil), for the determination of pharmaceuticals and metabolites and subsequent study of environmental risk. The combined method presented in this study had was successfully employed for the screening and quantification of pharmacological compounds and metabolites present in hospital effluents, with heterogeneous complexity characteristics. The screening method enabled the identification of five metabolites and 45 active principles, from which 24 were classified as suspect and 22 confirmed with standards. The quantification method had a linear response for 35 compounds and it was possible to quantify 22 analytes present in the samples, in a range from 1.17 µg L-1 to 239.64 µg L-1 . Furthermore, the direct injection analysis method presented in this study was successfully employed for the quantification of 35 compounds, of which up to 7 presented values above the LOQ of the method in hospital effluent. The HC samples showed concentrations in a range of 3.02 µg L-1 to 235.18 µg L-1 . There are indications of climatic conditions influence regarding to the concentration of drugs present in the effluent. The environmental risk assessment provided an RQ value > 1 for several compounds quantified in the HA and HB samples, with RQmix in the order of 30x106 for HA and 20x106 for HB. The RQmix for the samples from HC were in the order of 8x104 and 2x105 , respectively on winter and summer. The effluents from the three evaluated hospitals present an environmental risk for aquatic species and small rodents, based on the results of RQ and RQmix, and contribute to the fate and persistence of drugs in the environment.